Different Perspectives: A Study of Probabilities and Likelihoods of Brazilian Universities Upgrading in the National Evaluation System - Barbosa, Estela Capelas; Quoniam, Luc; Maccari, Emerson; Nogueira Ferraz, Renato Ribeiro (Frontiers in Education, 2017)
In the past few decades, the interaction between science and society has changed its nature. With this change, the reputation of academic institutions became important in all countries around the globe. In Brazil, the Coordination of Betterment of People in Higher Education (CAPES) is the governmental organ responsible for the process of evaluation of higher education, which produces a report and attributes grades to all Post-Graduate Programs around the nation. In this paper, we have analyzed the universe of attributed grades from 2004 to 2013. Our goal was to find patterns and possible biases in the evaluation process. We have found two important deviations. One refers to the higher likelihood of obtaining a higher grade if you are located in the South East. The other has to do with the administrative nature of universities. Public institutions are privileged by CAPES in the process of evaluation. Particularly, Federal universities are many times more likely to achieve higher grades in some cases. This produces a disincentive to newer and private institutions, which have been fulfilling the role of expanding higher education in Brazil.